Exploring the reasons of unsuccessful attempts in examination during postgraduate clinical training - Ehsan, Sumera; Fazal, Muhammad Owais; Ayub, Ayesha; Badar, Beenish (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the reasons of unsuccessful attempt in examination during postgraduate clinical training in Pakistan. Method: The qualitative, exploratory study was conducted at the Allied Hospital, Faisalabad, Pakistan, from December 1, 2022, to February 25, 2023, and comprised postgraduate trainees from different departments who had at least one unsuccessful attempt in examination during their residency programme. Data was collected through direct interviews that were recorded. The data was subjected to thematic narrative analysis. Results: Of the 14 participants, 10(71.4%) were males and 4(28.5%) were females. The maximum number of unsuccessful attempts were 7(7%), followed by 6(14%), 4(7%), 3(14%), 2(42%) and 11(14%). There were 3 main themes; personal factors, training factors, and exam factors. All the themes had subthemes. Conclusion: At the start of the residency programme, postgraduate trainees must be provided with adequate guidance, and a support system must be present during the programme to help them cope with the stress during training. Key Words: Medical residents, Surgical residents, Training, Postgraduation, Reasons, Unsuccessful.